Sequencing of cerebrospinal fluid in non‐small‐cell lung cancer patients with leptomeningeal metastasis: A systematic review - Tianqi Gao; Fengxi Chen; Man Li (Cancer Medicine)
Abstract Leptomeningeal metastasis (LM) refers to the dissemination of malignant cells in the subarachnoid space, pia, and arachnoid mater and is a severe condition associated with metastatic solid tumors. The most common solid tumor that develops into LM is lung cancer and the incidence increased in patients with advanced non‐small‐cell lung cancer (NSCLC) with targetable mutations. However, tissue biopsy of LM is inaccessible, leading to the paucity of genomic profiles of LM to guide targeted treatments and explore biological mechanisms. In recent years, liquid biopsy is considered a minimally invasive and dynamic method to trace the genomic alterations of cancer cells and some studies started to perform sequencing of cerebrospinal fluid (CSF) in patients with LM to reveal the targeted mutations and genomic profiles. In this review, we focused on studies performed sequencing of CSF in NSCLC patients with LM and summarized the sequencing results and their commonality. As the only way to reveal the genomic landscapes of LM, our review provided evidence that sequencing of CSF is a promising management method in LM patients to dynamically guide target therapy and monitor intracranial tumor response. Furthermore, it reveals a unique genomic profile of LM including driver genes, drug‐resistant mutations, and a number of copy number variations. Sequencing of CSF in LM patients seems to provide more comprehensive genomic information than we expected and the biological significance behind the genomic alternations needs further study.